Development of a Web-Based Administrative Information System for Owned Enterprises (BUMDes) in Macolliloloe Village - Astry Astry; Dyah Darma; Satria Gunawan Zain; Akhyar Muchtar (Journal of Computer Engineering, Electronics and Information Technology, 2022)
This study aims to determine the results of developing a web-based BUMDes administrative information system in Macolliloloe Village and testing a website-based BUMDes administrative information system using the ISO 25010 standard. This study is a Research and Development (RD) research. It uses a prototype development model consisting of the stage of gathering requirements, building prototypes, evaluating prototypes, coding the system, testing the system, evaluating the system, and using the system and collecting data in this study using interviews, questionnaires, measurement software, and documentation. System testing in this study uses several quality standards for software development, namely ISO 25010, including the functional suitability aspect with the results of a decent and acceptable category, the performance efficiency aspect with class B results, the usability aspect with excellent category results, the reliability aspect with the acceptable category results. Received is worth 100% without errors and portability with very decent results. Based on the results of this study, a web-based BUMDes administrative information system development was produced in Macolliloloe Village. It could be used to manage BUMDes administration using the prototype method with aspects of the ISO 25010 standard.